2022
DOI: 10.1371/journal.pone.0271517
|View full text |Cite
|
Sign up to set email alerts
|

Face masks to prevent transmission of respiratory infections: Systematic review and meta-analysis of randomized controlled trials on face mask use

Abstract: Objectives To examine the use of face mask intervention in mitigating the risk of spreading respiratory infections and whether the effect of face mask intervention differs in different exposure settings and age groups. Design Systematic review and meta-analysis. We evaluated the risk of bias using the Cochrane Risk of Bias 2 tool (ROB2). Data sources We searched PubMed, Embase, Cochrane Central Register of Controlled Trials, and Web of Science were searched for randomized controlled trials investigating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…Although smaller in the other countries, the gap was still almost 30 percentage points in Nigeria and 20 percentage points in Bangladesh. In Bangladesh, experimentally induced differences in facemask compliance of approximately 30 percentage points were associated with a reduction in symptomatic seroprevalence of COVID-19 by over 11% [ 5 ]. Other studies have also generally found that high levels of compliance are needed to reduce transmission at the community level [ 4 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although smaller in the other countries, the gap was still almost 30 percentage points in Nigeria and 20 percentage points in Bangladesh. In Bangladesh, experimentally induced differences in facemask compliance of approximately 30 percentage points were associated with a reduction in symptomatic seroprevalence of COVID-19 by over 11% [ 5 ]. Other studies have also generally found that high levels of compliance are needed to reduce transmission at the community level [ 4 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be especially true in LMIC settings where resources to enforce mandates may be more limited. A recent large scale randomized trial implemented in Bangladesh to test strategies to increase mask usage found that the free provision alone of masks had only a small effect on uptake but that periodic monitoring in public places led to large increases in mask-wearing and that these effects were sustained over long periods [ 5 ]. The monitoring intervention also led to increases in other preventive behaviors, namely physical distancing, which further points to the importance of social norms and pro-social learning in the promotion of public health measures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[34][35][36] Nonetheless, the evidence supporting the use of face masks in children is almost primarily based on studies of adults. [37][38][39] and there remains a lack of consensus around the effectiveness of face masks in preventing pediatric respiratory viral transmission. [40][41][42] Following evolving guidance from the Centers for Disease Control and Prevention (CDC) and the American Academy of Pediatrics, most schools have relaxed masking recommendations in communities where COVID-19 transmission rates and hospital admission rates are low and hospitals have sufficient capacity.…”
Section: Introductionmentioning
confidence: 99%